UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KENAKALAN PESERTA DIDIK DI SEKOLAH DASAR NEGERI BULUREJO 2 DIWEK JOMBANG - Eny Fatimatuszuhro Pahlawati; Shofwatal Qolbiyyah; Siti Aminatuzzuhroh (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
The aim of this research is to find out how Islamic Religious Education teachers try to overcome student delinquency at the Bulurejo 2 Diwek Jombang State Elementary School. This type of research is qualitative research, using a descriptive approach. The data collection technique is through observation, interviews and documentation. Meanwhile, the data analysis technique uses qualitative descriptive analysis which is carried out in depth through 3 stages, namely: data reduction, data presentation, and drawing conclusions or verification. The results of the research show that the efforts of Islamic religious education teachers to overcome student delinquency at the Bulurejo 2 Diwek Jombang State Elementary School were carried out by collaborating with students' parents, providing advice, guidance, motivating students, approaching and reprimanding students who commit a violation. Obstacles experienced by Islamic religious education teachers in dealing with student delinquency at Bulurejo 2 Diwek Jombang State Elementary School include: lack of cooperation between teachers and parents of students, limited time in providing guidance to students, students not being open with teachers, and free association of students outside school hours.